Time trends and geographical variation in prescribing of antibiotics in England 1998-2017 - Curtis, H; Walker, A; Mahtani, K; Goldacre, B (Oxford University Press, 2018)
Background Reducing antibiotic overuse is a key NHS priority. The majority of antibiotics are prescribed in primary care. Objectives To describe antibiotic prescribing trends in NHS England primary care for the years 1998–2017 using various measures. We investigated trends and variation between practices and geographical areas, out-of-hours prescribing, and seasonality. Methods We used publicly available prescribing datasets and calculated antibiotic prescribing rates per 1000 age–sex-adjusted population units, percentage prescribed as broad-spectrum, and course length. We report national time trends for 1998–2016, geographical variation across 2017 and variation trends for 2010–17. We calculated percentiles and ranges, and plotted maps. Results The overall rate of antibiotic prescribing has reduced by 18% since 2010, with the steepest decline since 2013. The percentage prescribed as broad-spectrum declined since 2006, from 18.0 to 8.4. Between the best and worst Clinical Commissioning Groups (CCGs) there was 2-fold variation for total antibiotic prescribing, but 7-fold variation for cephalosporins. Variation across general practices has declined. The CCG to which a practice belongs accounted for 12.6% of current variation (P < 0.0001). Higher antibiotic prescribing was associated with greater practice size, proportion of patients >65 years or <18 years, ruralness and deprivation. Seasonal increases have been declining for most antibiotics. If every practice prescribed antibiotics at the lowest decile rate in 2017, 10.8 million fewer prescriptions could have been issued (34%). Compared with standard practices, out-of-hours practices prescribed a greater proportion of broad-spectrum antibiotics. Conclusions Despite a general trend towards more optimal antibiotic prescribing, considerable geographical variation persists across England’s practices and CCGs.